Synergy Between Government and Community in Preventing Savanna Fires: An Environmental Law Review - Maureen Vinalia Plaikoil; Alfando Lorens Juku Aja; Clarita Adecristi Tamu Ina (IHSA Institute, 2025)
Forest and grassland fires in East Sumba Regency have continued to increase to catastrophic levels. From the beginning to the middle of 2025 alone, there have been more than five cases of savanna fires in several different villages. To date, there has been no court ruling or action by the local government in East Sumba Regency to impose sanctions on those responsible for burning savanna grasslands. This study employs a normative-empirical legal method. The approaches used in this study include the statute approach to analyse relevant legal provisions and the socio-legal approach to assess the application of these provisions in practice through interviews and observations. Savanna fires in Sumba are prohibited by environmental law, but due to weak enforcement, the justification of local wisdom, and the difficulty of proving guilt, almost all cases end without sanctions, even though thousands of hectares of savanna are burned each year, causing harm to the community. Local governments are required to establish technical regulations for savannas due to their unique and vulnerable nature, whether in the form of district regulations or village regulations. The best approach is a combination of education, regulation, conservation, and law enforcement